From fire rain to rebellion: reasserting ethnic identity through narrative - Andersen, Peter B.(ed.); Carrin, Marine (ed.); Soren, Santosh K. (New Delhi Manohar, 2011)
The Santals, a major tribal group of India, are known for theirHul, an important rebellion led by charismatic heroes in 1855-7,and analysed by subaltern historians as conveying political andintellectual concerns, such as peasant consciousness, pertinent topost-colonial India. After the rebellion, Christian missions wereestablished in the Santal Parganas, among them, the ScandinavianLutheran missionaries considered the Santals as a nation and wantedto create a Santal National Church, and their presence contributedto reinforce Santal identity. This volume presents selections fromRev. P.O. Boddings collection of Santal folklorethree thousandpages now found in the Oslo University Librarywhich he collectedfrom 1892 to around 1927. The editors have selectednarrativesmythological and historicalwhich Bodding leftunpublished. The introduction of writing allowed another texture ofknowledge to emerge from the colonial encounter, expressing itselfthrough these narratives. Boddings collections were done by Santalswhom he trained, but at least one of them, Sagram Murmu meritsconsideration as an author in his own right. The choice of textspresented here shows us how the Santals recast their traditions asknowledge, as a body of institutions and laws, and as a way oflife. These texts contribute to inform how marginalized people,such as the Santals, experienced colonial modernity but succeededin negotiating for themselves the potential of nationalde-colonisation. The book aims at documenting subaltern pasts,allowing their re-appropriation by the Santal themselves.
Keywords: Santhal tribe-India